2011
DOI: 10.1002/qre.1256
|View full text |Cite
|
Sign up to set email alerts
|

A Review and perspective on surveillance of Bernoulli processes

Abstract: Bernoulli processes have been monitored using a wide variety of techniques in statistical process control. The data consist of information on successive items classified as conforming (nondefective) or nonconforming (defective). In some cases, the probability of obtaining a nonconforming item is very small; this is known as a high quality process. This area of statistical process control is also applied to health-related monitoring, where the incidence rate of a medical problem such as a congenital malformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 112 publications
1
50
0
Order By: Relevance
“…For these high‐quality processes, many control charting methods have been recommended for monitoring the proportion nonconforming. As highlighted in Szarka and Woodall, the sampled items in these processes are often represented by a Bernoulli process; that is, the items are independently classified as conforming or nonconforming. In addition, Szarka and Woodall stated that the in‐control value of p , p 0 , is typically assumed to be known.…”
Section: Introductionmentioning
confidence: 99%
“…For these high‐quality processes, many control charting methods have been recommended for monitoring the proportion nonconforming. As highlighted in Szarka and Woodall, the sampled items in these processes are often represented by a Bernoulli process; that is, the items are independently classified as conforming or nonconforming. In addition, Szarka and Woodall stated that the in‐control value of p , p 0 , is typically assumed to be known.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been proposed for monitoring rare event data; see Woodall and Driscoll, Szarka and Woodall, and Ali et al …”
Section: Resultsmentioning
confidence: 99%
“…When they are results from Bernoulli experiments, the n p and p charts may be applied to monitor the stability of nonconforming proportion . Good review papers about attribute charts can be found in the literature as these written by Szarka and Woodall and Woodall . Some recent contributions on n p or p charts varying estimator, sampling, or decision scheme can be cited .…”
Section: Introductionmentioning
confidence: 99%